Influence of Tryptophan Modification upon Digestion of Antithrombin III by Elastase - Scully, M F; Shah, N; Ellis, V; Kakkar, V V (Thrombosis and Haemostasis, 1991)
Chemical modification of tryptophan residues in antithrombin III by dimethyl (2-hydroxy-5-nitrobenzyl) sulfonium bromide (HNBSB) generates products with similar levels of modification (equivalent to 0.9 mole 2-hydroxy-5-nitrobenzyl [HNB] incorporated/mole of antithrombin III) but with high or low affinity for heparin-Sepharose. Upon digestion with pancreatic or neutrophil elastase the low affinity forms generate a product of molecular weight form (55 kDa) not seen in digests of native antithrombin III or modified forms with high affinity for heparin. When measured as loss of activity the obserued rate of digestion of the latter in the absence of heparin was more rapid than that of native antithrombin III. The differences in digestion are considered to be related to conformation at differences between the various forms.